Huge Pyogenic Granuloma of the Penis - Fatih Akbulut; Tugba Akbulut; Faruk Kucukdurmaz; Erkan Sonmezay; Abdulmuttalip Simsek; Gokhan Gurbuz (Case Reports in Urology)
Pyogenic granulomas are benign vascular disorders of the skin and mucose membranes, generally developed by trauma and irritation. The lesions are generally small. They are most commonly seen in the skin and oral mucosa and rarely seen on penis. We present the case of a huge pyogenic granuloma on the penis.